2008
DOI: 10.1902/jop.2008.070398
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Specific Development of Periodontal Disease Is Associated With Increased Levels of Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia in Subgingival Plaque

Abstract: The symbiotic effects of P. gingivalis, T. denticola, and T. forsythia, which coaggregate and exist concomitantly in subgingival biofilms, may be associated with the local development of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
60
2
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 22 publications
11
60
2
12
Order By: Relevance
“…Interestingly, the analysis of red complex periodontopathogens individually and as a group resulted in similar results, probably due to their simultaneous occurrence in most of the patients. Indeed, the red complex periodontopathogens were shown to exist as a consortium (29,32,49) and to exhibit synergistic virulence in a rat model of polymicrobial periodontal infection (24). In accordance, our results demonstrate an increase in IL-1␤ levels associated with the simultaneous occurrence of two or three red complex species, suggesting an increasing pathogenic proinflammatory role for these bacteria.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the analysis of red complex periodontopathogens individually and as a group resulted in similar results, probably due to their simultaneous occurrence in most of the patients. Indeed, the red complex periodontopathogens were shown to exist as a consortium (29,32,49) and to exhibit synergistic virulence in a rat model of polymicrobial periodontal infection (24). In accordance, our results demonstrate an increase in IL-1␤ levels associated with the simultaneous occurrence of two or three red complex species, suggesting an increasing pathogenic proinflammatory role for these bacteria.…”
Section: Discussionsupporting
confidence: 86%
“…denticola is thought to be an important periodontal pathogen, based upon observations that it is frequently detected in active periodontal lesions (Mineoka et al, 2008), and has been defined as a component of the socalled red complex that includes P. gingivalis and T. forsythia. In PCR-based methods of bacterial detection, T. denticola and other Treponema phylotypes are almost always isolated from infected root canals (Montagner et al, 2010) and periodontal pockets (Byrne et al, 2009), and within a single pocket there may be multiple phylotypes (Choi et al, 1994;Dewhirst et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria are usually found together in periodontal pockets and it is suggested that they may cause destruction of the periodontal tissue in a cooperative manner [5][6][7]. On the other hand, different immunological aspects are suspected to play roles in the development and progression of periodontal diseases [8].…”
mentioning
confidence: 99%